Quality Assurance Units in Nigerian Public Tertiary Institutions: Problems and Ways Forward - Conrad Ugochukwu UKOZOR (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The quest by the federal government of Nigeria to achieve quality tertiary education in line with global best practices established some agencies and commissions to help in quality assurance in the various higher institutions such National Universities Commission [NUC], the National Commission for Colleges of Education [NCCE] and the National Board for Technical Education [NBTE]. These regulatory bodies in the bid to attain internal quality assurance directed various institutions under their watch to establish departments or units of quality assurance to help strengthen the internal quality assurance programme of the regulatory bodies. These internal quality assurance units since taking off in some higher institutions, especially in the public universities in Nigeria have been facing some challenges. This paper discussed the problems hindering the effective service delivery of quality assurance units or departments in public tertiary institutions. The paper depends on secondary data and primary data. These data were sourced from both online and print published and unpublished works of literature. Some of these problems facing the quality assurance directorate/ units in Nigerian tertiary institutions include inadequate funding, inadequately trained quality assurance officers, and poor capacity-building programme, inadequate infrastructural facilities and working tools. To ensure effective quality assurance units in Nigerian tertiary institutions, the following have been suggested: adequate funding, employment of adequate quality assurance officers, provision of adequate infrastructural facilities, working tools and effective capacity development programme.